2007
DOI: 10.1128/jb.01600-06
|View full text |Cite
|
Sign up to set email alerts
|

Porins Are Required for Uptake of Phosphates by Mycobacterium smegmatis

Abstract: Phosphorus is an essential nutrient, but how phosphates cross the mycobacterial cell wall is unknown. Phosphatase activity in whole cells of Mycobacterium smegmatis was significantly lower than that in lysed cells, indicating that access to the substrate was restricted. The loss of the outer membrane (OM) porin MspA also reduced the phosphatase activity in whole cells compared to that in lysed cells. A similar result was obtained for M. smegmatis that overexpressed endogenous alkaline phosphatase, indicating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…smegmatis-The observation that Rv1698 forms an apparently nonspecific protein channel in a similar manner as MspA (9,10,31) raised the question why Rv1698 completely restored the susceptibility of the M. smegmatis mspA porin mutant to antibiotics (Fig. 1), whereas glucose diffusion was slow compared with MspA (Fig.…”
Section: Rv1698 Can Partially Substitute For the Porin Mspa Of Mmentioning
confidence: 99%
“…smegmatis-The observation that Rv1698 forms an apparently nonspecific protein channel in a similar manner as MspA (9,10,31) raised the question why Rv1698 completely restored the susceptibility of the M. smegmatis mspA porin mutant to antibiotics (Fig. 1), whereas glucose diffusion was slow compared with MspA (Fig.…”
Section: Rv1698 Can Partially Substitute For the Porin Mspa Of Mmentioning
confidence: 99%
“…Hydrophilic substances cross this membrane via porins, whose importance in phosphate uptake was highlighted recently (530).…”
Section: Transport Across the Outer Membranementioning
confidence: 99%
“…Since MspA could not be expressed in M. smegmatis above wild-type levels (Stephan et al, 2005), it is also not clear whether the influx of nutrients really limits the growth rate of wild-type mycobacteria as suggested earlier (Jarlier & Nikaido, 1990). The fact that the lack of the MspA and MspC porins also caused a reduced uptake of phosphates and slower growth on low-phosphate plates (Wolschendorf et al, 2007) indeed suggested that the slow uptake of essential hydrophilic nutrients other than the carbon source may also contribute to the slow growth of M. smegmatis porin mutants.…”
Section: Transport Across Mycobacterial Outer Membranesmentioning
confidence: 93%
“…Note that no experimental data exist for either the spatial distribution of the extractable lipids, or the confirmations and exact locations of the mycolic acids. The porin MspA mediates the uptake of small and hydrophilic nutrients such as sugars (Stephan et al, 2005) and phosphates (Wolschendorf et al, 2007) across the outer membrane of M. smegmatis. The representation of MspA is based on its crystal structure (Faller et al, 2004) and was created using the visualization software PyMol (DeLano Scientific).…”
Section: Permeability Barriers In Mycobacterial Cell Envelopesmentioning
confidence: 99%
See 1 more Smart Citation